Psychological Health’s Effect on Education - Mahdi, Assist. Prof. Dr. Sanaa Mohammed Mahdi (Sulaimani Journal for Humanities, 2026)
Education is very important in the world; to educate means to give new life so it is necessary to pursuit the students and not leave them in the lurch. University students represent the main pillar of the future of society as they are a vital goal that various educational institutions seek to achieve. Hence, we have to indicate the problems they face specifically their psychological health that affect their academic performance. The university stage is an important stage in consolidating habits, skills and behavioral patterns in the personality of students, and crystallizing values, trends, and ideas. Hence, very important to shed light on the psychological factors that influence the level of academic performance, including self-confidence, depression, anxiety, and motivation for achievement. The result of which confirms that feelings of depression negatively affect the level of academic performance. The student's psychological state occupies a large part of his thinking, and occupies the mind with matters outside of study. This bad psychological state leads to the student falling into the clutches of failure, and many male/ female students are exposed to academic failure because they go through some bad psychological circumstances and states. Definitely, the psychological state that occupies the minds of the students and makes them turn away from the education; it must be followed by unusual reactions that affect the student’s educational career who with a psychological condition knows in advance that he will fail which leads him becoming agitated and his behavior abnormal.
Keywords: student; failure; depression; anxiety; self confidence; success